Methodological development of sesonal cooling energy needs by introducing ground-cooling systems - Oliveira Panão, Marta (2011)
In past years, building professionals increased their interest on passive systems as sustainable solutions to reduce energy needs. This has been driven by the building certification program and new Portuguese building thermal code enacted in 2006. For residential and small office buildings, the methodology adopted is a seasonal quasi-stationary approach for calculating cooling energy following EN ISO 13790:2007. However, this method lacks specific recommendations for accounting passive cooling systems, namely ground-cooling systems. In this paper, the ground-heat exchanger contribution is included in the energy needs method. This development is sustained by measurements obtained in the ground-heat exchanger running on Solar XXI office building at LNEG campus, complemented by simplified and Fourier theoretical formulations. The horizontal ground-heat exchanger at Solar XXI is constituted by 32 concrete ducts, with a 30 cm diameter and buried 4.6 m deep. The air entrance is made from a feeding well about 15 m away from the building and its functioning during summer warm days supplies cool air for room offices.